Modelling of Gassing for VRLA OPzV (gel) Battery at 25°C - Hayat, Jibran; Fuengwarodsakul, Nisai H.; Muenderlein, Jeanette; Ruewald, Timo (Applied Science and Engineering Progress, 2019)
In order to increase the performance of the Energy Management System (EMS) for the M5BAT (Modular Multi-Megawatt Multi-Technology Middle Voltage Battery Storage System), with a size of 5 MW and to take full economic advantage of the various lead-acid batteries, battery models are implemented. Based on such models, a technology specific and favorable operation can be assured. For improving the model an experimental study of gassing has been conducted on the Sonnenschein A602 OPzV VRLA (gel) battery. Single electrode potentials have been observed and evaluated at different current rates at a regulated temperature of 25°C. Parameters such as the symmetry factor and current exchange density have been obtained from the measured data. Matlab/Simulink has been used to model the process of gassing using Tafel´s equations.